Cytokine-enhanced maturation and migration to the lymph nodes of a human dying melanoma cell-loaded dendritic cell vaccine - Pizzurro, Gabriela Andrea (2015)
Dendritic cells (DCs) are professional APCs used for the development of cancer vaccines because of their ability to activate adaptive immune responses. Previously, we designed the DC/Apo-Nec vaccine using human DCs loaded with dying melanoma cells that primed Ag-specific cytotoxic T cells. Here, we evaluate the effect of a standard pro-inflammatory cytokine cocktail (CC) and adjuvants on DC/Apo-Nec maturation and migration. CC addition to the vaccine coculture allowed efficient Ag uptake while attaining strong vaccine maturation with an immunostimulatory profile. The use of CC not only increased CCR7 expression and the vaccine chemokine responsiveness but also upregulated matrix metalloproteinase-9 secretion, which regulated its invasive migration in vitro. Neither IL-6 nor prostaglandin E2 had a negative effect on vaccine preparation. In fact, all CC components were necessary for complete vaccine maturation. Subcutaneously injected DC/ApoNec vaccine migrated rapidly to draining LNs in nude mice, accumulating regionally after 48 h. The migrating cells of the CC-matured vaccine augmented in proportion and range of distribution, an effect that increased further with the topical administration of imiquimod cream. The migrating proportion of human DCs was detected in draining LNs for at least 9 days after injection. The addition of CC during DC/Apo-Nec preparation enhanced vaccine performance by improving maturation and response to LN signals and by conferring a motile and invasive vaccine phenotype both in vitro and in vivo. More importantly, the vaccine could be combined with different adjuvants. Therefore, this DC-based vaccine design shows great potential value for clinical translation.